Mealybug Vryburgia trionymoides (DeLotto) (Pseudococcidae) - Ian Stocks (EDIS)
On several occasions in 2011, succulents for sale at retail stores in Florida were found with infestations of the mealybug Vryburgia trionymoides DeLotto. A traceback revealed that the succulents originated in California, where this mealybug is known as an occasional greenhouse pest. Specimens intercepted or found in retail stores often were well-hidden in the axillary region near the stem, making detection more challenging. An untreated infestation can kill a plant, there are no published reports of economic losses caused by this species. This 2-page fact sheet was written by Ian Stocks, and published by the UF Department of Entomology and Nematology, April 2013.